Strengthening the quality of longitudinal research into cognitive-communication recovery after traumatic brain injury: A systematic review. (2nd January 2017) - Elbourn, Elise; Togher, Leanne; Kenny, Belinda; Power, Emma
Abstract: Purpose : (i) To systematically review longitudinal and prognostic studies relating to the trajectory of cognitive-communication recovery after TBI and (ii) to provide recommendations to strengthen future research. Method : Thirteen health literature databases were accessed up until July 2014. Main measures : Articles were screened systematically against pre-determined inclusion and exclusion criteria. Quality reviews were performed on the selected articles using a modified Downs & Black Rating Scale. Two independent reviewers performed the reviews. Result : Sixteen longitudinal and prognostic articles met the inclusion criteria. There was evidence of either maintenance or improvement of cognitive-communication skills during the first 3 years post-injury. However, the studies did not provide detailed recovery trajectories, by failing to evaluate numerous data points over time. No studies evaluated recovery beyond 3 years post-injury. Injury severity, lesion location, brain volume loss and conversation skills may predict specific cognitive-communication outcomes. There was high variability in study characteristics and measures. Conclusion : There is currently scarce evidence regarding cognitive-communication recovery and prognosis. People with TBI may recover or maintain pre-morbid cognitive-communication skills during the early rehabilitation stage. Further research detailing the recovery trajectory with a view to evaluating predictive factors is strongly indicated. Guidelines for future research are provided.